Alterations in physicochemical parameters of water and the growth performance of juvenile beluga Huso huso in earthen ponds - Hashem Noferesti; Hojatollah Jafaryan; Rahman Patimar; Hossein Adineh (تغذیه آبزیان, 2024)
Introduction: Sturgeon, renowned for its prized caviar, plays a vital role in aquatic ecosystems and holds significant economic value. Breeding sturgeon is a delicate process that necessitates specific conditions for success. Factors such as temperature, dissolved oxygen levels, pH, and ammonia concentration in water quality substantially impact sturgeon breeding outcomes. Ensuring the ideal water quality is critical for sturgeon populations' health and successful breeding. Understanding and efficiently controlling these factors is crucial to guaranteeing the long-term viability of sturgeon populations and the preservation of this symbolic animal. This study investigates the growth indices and physicochemical water parameters in earthen ponds to raise juvenile beluga, Huso huso.Materials and Methods: Four earthen ponds, each covering an area of 2 hectares with an average depth of 2 meters and a rectangular shape, were utilized for rearing beluga at the Shahid Marjani Breeding Center, Northeastern Iran. The test period lasted 45 days. The growth performance and water physicochemical parameters were measured during six weekly treatments from mid-March 2013 to mid-April 2014. Fish sampling was carried out using a trawl net at specific time intervals of the experiment. The length and weight of the fry were recorded, followed by the dissection of the fish. The length and weight of the digestive tract were measured in both full and empty states. Water samples were collected weekly, and physicochemical parameters were analyzed using standard methods.Results and Discussion: Temperature (12.5 to 16.6°C), turbidity (0.50 to 50.92 NTU), dissolved oxygen (10.90 to 6.25 mg/L), pH (7.62 to 8.92), alkalinity (160 to 223 mg/L), phosphate (0.17 to 0.73 mg/L), nitrate (0.24 to 1.67 mg/L), and electrical conductivity (1240 to 1342 µmhos/cm) levels for the growth of beluga were within the optimal ranges. Additionally, the growth pattern of the sturgeon juveniles was characterized by negative allometry, indicating that as the fish grew, their weight increased at a slower rate compared to their length. There was a significant elevation in total length and weight over time, demonstrating effective growth conditions during the study period. The total length and weight of the fingerlings showed significant upraise over time (p<0.05). The highest total length (36.70 ± 7.47 mm), weight (2674.54 ± 678.04 mg) and gastrosomatic weight (431.35 ± 75.97 mg) of fingerlings were recorded during the sixth sampling period. However, the highest condition factor (0.94 ± 1.11) was measured during the second sampling period (p<0.05).Conclusion: The results indicated that precise water quality management and continuous monitoring of its parameters, especially in sturgeon farming, are essential and can help improve growth conditions and reduce mortality rates. Ensuring optimal environmental conditions, particularly in earthen ponds, can increase productivity in the sturgeon fish farming industry.Funding: This research did not receive a specific grant from any funding agency in the public, commercial, or not-for-profit sectors.Conflicts of interest: The authors have no conflicts of interest to declare.Acknowledgments: The authors would like to express gratitude for the valuable assistance provided by the officials and employees of the Shahid Marjani Sturgeon Propagation Centre.